New Technology of Functional Bakery Products - Olga L. Ladnova; Svetlana Ya. Koryachkina; Vladimir P. Koryachkin; Larisa S. Bolshakova (Техника и технология пищевых производств)
Peas (Pisum sativum L.) are rich in protein, B vitamins, and dietary fiber, represented by hemicellulose and pectins. In terms of amino acids, pea proteins are as close to the reference protein as possible. The limiting amino acids of pea protein are sulfur-containing, i.e., methionine and cysteine. Peas are also rich in lysine, which is the limiting amino acid for wheat flour. Therefore, products of pea processing can expand the range of commercial high-protein foods, including functional bakery products. The research objective was to develop a technology for functional bread from a mix of wholemeal pea flour and wheat gluten. The study featured baking wheat flour, wheat gluten, wholemeal pea flour of San Cipriano and Vega varieties, dough samples, and ready-made bread. The carbohydrate-amylase complex of flour was studied using an Amilotest AT-97 device. The starch content was determined by the polarimetric method. The spectrophotometric method served to test the flower samples for protein while the Kjeldahl method was applied to the bread samples. The rheological properties of the dough were studied on a Reotest 2 viscometer. The sensory evaluation relied on a panel of experts, and the chemical composition was revealed by calculation and analytically. The wholemeal pea flour had a lower starch gel viscosity compared to the wheat flour sample. A greater amount of flour added during kneading increased the viscosity of the resulting dough. The acidity was rather high: 7.2 and 9.4 degrees for San Cipriano and Vega samples, respectively, and so was the autolytic activity (≤ 80 s). These useful qualities made it possible to reduce the technological process by 115 and 145 min. The resulting bread demonstrated good physical, chemical, and sensory indicators. The high-protein raw materials increased the protein content in bread by 41.9–46.4%, compared to the control sample, which equaled 33.1–34.2% of the recommended daily intake per 100 g of bread. The optimal ratio of wholemeal high-protein pea flour and wheat gluten was 20/80 for the San Cipriano samples and 30/70 for the Vega variety.